2018
DOI: 10.4081/jphia.2018.708
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nutritional supplementation on body mass index and CD4 count among adult people living with HIV AIDS on antiretroviral treatment in Conakry, Guinea

Abstract: Whereas the HIV prevalence in Guinea is among the lowest in Africa, many PLHIV in Guinea are malnourished. This study assessed the effect of a nutritional supplementation program on body mass index and CD4 count among adult PLHIV on ART. Study participants were PLHIV who came for consultation in the study sites between May and July 2016. The data came from two sources: retrospectively from participants’ medical records and interviews at the time of recruitment into the study. About six months before they were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…This finding is similar to a study conducted in Conakry, Guinea, where an increase in the CD4 count and mean BMI of PLHIV on ART was observed after six months of supplementation with Corn- Soy, and oil [ 48 ]. In Nigeria, Amlogu et al.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to a study conducted in Conakry, Guinea, where an increase in the CD4 count and mean BMI of PLHIV on ART was observed after six months of supplementation with Corn- Soy, and oil [ 48 ]. In Nigeria, Amlogu et al.…”
Section: Discussionsupporting
confidence: 90%
“…This was contrary to Palar et al ’s (2017) study whose findings stated that comprehensive and medically appropriate food support is associated with improved health status of people living with HIV/AIDS by assessing paired outcomes at baseline and six months of a community-based food support intervention programme. Studies have also reported improvement in weight conditions, BMI, CD4, ART adherence, quality of life and overall health status, and reduction in loss to follow-up of people living with HIV/AIDS on NSPs (Audain et al , 2015; Booysen et al , 2016; Botros et al , 2013; Hong et al , 2018; Koethe et al , 2018; McCoy et al , 2017; Mensah et al , 2015; Odong et al , 2015; Sidibé et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the observations at the hospital showed that most patients with HIV and AIDS had normal and low BMIs. This followed the respondents' CD4 counts, which showed <200 µ/l in as much as 40%; even the patients' minimum CD4 count was very low, at 3 µ/l (Sidibé et al, 2018).…”
Section: Functional Statusmentioning
confidence: 64%
“…Other studies have suggested that there is a significant and positive correlation between the CD4 cell count and weight gain so that the QoL of patients is also better. Direct or indirect damage to CD4+ T cells is very influential because CD4+ T cells are needed for the immune system to function properly (Sidibé et al, 2018). If HIV has killed CD4+ T cells so that the number of cells has shrunk to <200 µ/l blood, then immunity will be lost and, as a result, AIDS will occur.…”
Section: Relationship Of Characteristics and Clinical Status With Quamentioning
confidence: 99%